2021
DOI: 10.3389/fcomm.2021.661930
|View full text |Cite
|
Sign up to set email alerts
|

Health Communication and Inter-professional Care in Context of Multimorbidity Management: Assessment of Health Professional Curricular Focus in India

Abstract: To meet the long term care demands of chronic diseases as well as multimorbidity, healthcare providers from different disciplines need to work collaboratively in practice. This requires healthcare providers to be appropriately trained on delivery of inter-professional care (IPC) and health communication aspects during formative professional years. In this study, we have looked at the prevailing undergraduate and postgraduate healthcare professional curricula to understand the focus on health communication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It highlights the need for unique and a patient-centric approach in primary care settings to treat patients with multiple chronic conditions. Evidence suggested that the Indian healthcare system which is a single-disease paradigm primarily focused on acute care may not be adequate in the treatment of older people, particularly those living with multiple conditions [ 63 ]. Therefore, there is a need for more effective and patient-centric healthcare to tackle the complex interactions of chronic diseases or specific combinations of diseases that patients may accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…It highlights the need for unique and a patient-centric approach in primary care settings to treat patients with multiple chronic conditions. Evidence suggested that the Indian healthcare system which is a single-disease paradigm primarily focused on acute care may not be adequate in the treatment of older people, particularly those living with multiple conditions [ 63 ]. Therefore, there is a need for more effective and patient-centric healthcare to tackle the complex interactions of chronic diseases or specific combinations of diseases that patients may accumulate.…”
Section: Discussionmentioning
confidence: 99%